Driving, dementia and Australian physicians: primum non nocere?. Issue 6 (9th June 2013) - Carmody, J.; Traynor, V.; Iverson, D.; Marchetti, E.
Abstract Older Australians are increasingly reliant on automobiles as their sole form of transport. As our population is ageing and the prevalence of dementia is increasing, it is anticipated that the number of drivers with dementia will rise over time. Much of the literature relating to driving and dementia focuses on safety rather than mobility. The objective of this paper is to highlight several topical ethical issues that pertain to Australian drivers with dementia. It is recommended that future research, policy and practice should centre on the crucial mobility and transport needs of our senior citizens.